SISTEM PENGOLAHAN LIMBAH PADAT DAN CAIR DI RUMAH SAKIT UMUM KABANJAHE BERDASARKAN KEPMENKES 1204/MENKES/SK/X/2004 TENTANG PERSYARATAN KESEHATAN LINGKUNGAN RUMAH SAKIT TAHUN 2012 - Hariani .; wirsal hasan; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Processing system of solid and waste water at Kabanjahe General Hospital according based on the Kepmenkes 1204/Menkes/SK/X/2004 about hospital environtmental health requirments 2012. Hospital as a health care facility is a gathering place for the sick and healthy people, or it can be the transmission of the disease and allow the environmental pollution and health disturbance. To avoid the risks and the health disturbance, it is necessary to the implementation of environmental health in according to health regulation. The purpose of this research is to gain an overview of waste water processing system at the Kabanjahe General Hospital, resource availability and the comparison with existing regulations. The present study is a descriptive one intended to analyze the solid and waste water processing of Kabanjahe General Hospital in 2012. The object of the study is all of solid and waste water processor. The data were collected by interview and observation based on the Kepmenkes RI No. 1204 of 2004 and then analyzed descriptively. The results showed that the solid and liquid waste treatment is not in accordance with RI Kepmenkes No.1204 of 2004 (42.85% <80%). This can be seen from the scoring has been done, the temperature of incinerator <1000°C, no MoU with others, not do sterilization of shelter and radioactive waste is not handled according to the rules. The conclusion of this study is a processing of solid and waste water at the Kabanjahe General Hospital is not appropriate environmental the health requirements based on Kepmenkes RI No.1204 of 2004. Resource in processing solid and waste waters are not enough in number and function, so we need additional personnel, specific training for solid and waste water processing, the application of technical guidelines Waste Water Processing Plan and incinerator, conduct routine checks of wastewater composition and make a budget for the provision of rubbish bin which appropriate with health requirements. Keywords : System, Solid And Waste Water, Hospital, Kepmenkes